The development of novel synthetic methodologies for the preparation of glycosidase inhibitors - Malone, Aoife (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
Sugars with heteroatoms other than oxygen in the ring (e.g. iminosugars, thiosugars) are known to exhibit interesting biological activities and possess considerable therapeutic potential. Their biological activity can be principally attributed to their inhibitory effect on glycosyltransferases and glucosidases. Inhibition of these enzymes renders thiosugars and azasugars therapeutically useful against a range of diseases including diabetes, HIV, hepatitis and cancer.
Embargo End Date: 2022-01-01
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin, 2014